1994
DOI: 10.1002/hup.470090402
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of dental anxiety and effects of treatment with nitrous oxide and midazolam in dentally phobic patients

Abstract: The role of general anxiety measured by the Hospital Anxiety and Depression Scale (HADS), or the Spielberger Trait Anxiety scale, (STAI‐T) on dental anxiety (measured by the Corah Dental Anxiety Scale, the Kent Phobia Scale and by analogue ratings concerning specific procedures) of dentally phobic patients was examined using multiple regression analysis. HADS anxiety and STAI‐T scores were both significant predictors of Corah scores; whereas HADS depression and STAI‐T predicted Kent scores, which measure how c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
4
0
1
Order By: Relevance
“…In other words, the presence of S allele is suggestible to higher score on DAS-R scale, i.e. higher expression of dental anxiety, which supports the previously noticed relations between S allele 5-HTTLPR polymorphism and anxiety, anxious people and neuroticism ( 5 - 7 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In other words, the presence of S allele is suggestible to higher score on DAS-R scale, i.e. higher expression of dental anxiety, which supports the previously noticed relations between S allele 5-HTTLPR polymorphism and anxiety, anxious people and neuroticism ( 5 - 7 ).…”
Section: Discussionsupporting
confidence: 87%
“…in a meta-analysis of 44 studies found correlation between SLC6A4 gene polymorphism and personality dimensions of anxiety, although in subsequent research conducted on mentally healthy subjects no such correlation was found ( 39 ). On the other hand, numerous studies suggest the relation between neuroticism and dental anxiety ( 5 - 7 ), as well as a higher frequency of S allele in subjects suffering from depression and anxiety disorders ( 35 ). Halonen et al in their research found a significant and positive correlation between dental anxiety and neuroticism and a significant although negative correlation with extraversion ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a signifi cant positive correlation between dental anxiety and trait anxiety has also been reported. 11,22 This discrepancy might be explained by methodological issues. For example, studies cited above tested small samples of patients undergoing third molar removal surgery or other dental treatment, while our data were based on a large sample involving a general population.…”
Section: Discussionmentioning
confidence: 99%
“…La utilización de las benzodiacepinas por diferentes vías de administración (oral, rectal, intranasal, intravenosa) es frecuente y sobradamente conocida en la prevención de estos problemas [14][15][16][17] . Otra alternativa es el uso de óxido nitroso que también se muestra eficiente en la prevención de estos sucesos 16,18 . Otros profesionales obtienen una reducción sustancial de la ansiedad y el miedo dental a través de sencillas sesiones de reestructuración cognitiva, modificando las ideas negativas que los sujetos tienen, perdurando en el tiempo la reducción del miedo conseguida 17,[19][20][21][22] .…”
Section: Discussionunclassified